Die visioenêre verbeelding en die animering van die inheemse landskap - Kruger, Louis Lodewyk (University of the Free State, 2016)
This study deals with the incomprehensible visionary experience and the possible relationships it may have with the indigenous landscape. It was motivated by artistic research (in the form of video art and digital photomontages) into the visionary potential that may be imbedded in the outstretched Northern Cape landscape. The problem regarding the representation of the visionary experience is firstly explored through the analyses of relevant image traditions in the history of art. These image traditions include: the mystical, the sublime, the apocalyptical, and the mythological. The diverse visual strategies, which are at work in these image traditions, reveal the various ways that the image of the landscape can suggestively act as a medium of visionary insights. Some of these revelations include: the use of the circle and saturated colours to suggest mystical power in the image and to sometimes facilitate a visionary revelation; the use of paradox, negation (like sombre light and obscurity) and synaesthetic combinations in images as a means to overcome the complexity and incomprehensibility of the visionary phenomenon; and the use of figures in the landscape to suggest the presence or expectancy of an active, chaotic eruption of visionary power in the landscape. The ability of the image of the outstretched landscape (specifically the desert that evokes allusions to eternity) to awaken a visionary eruption in the imagination is suggested through the implementation of the abovementioned visual strategies. In such cases it seems as if the image of the landscape jumps foreword, as though animated. Aby Warburg‟s notion of image animation is analysed to examine the image‟s ability to awaken a cultural memory of the landscape through the imagination. The ways in which the use of some visual motifs in images of the landscape is capable of promoting the animation process, is explored. These visual motifs include: the form of the vortex as visual and landscape motif, in the appearance of whirlwinds and whirlpools. The capacity of the vortex‟s features of constant movement, transformation, and instability to animate images of the landscape, is evaluated in association with the fascination with the vortex form in the history of the visionary phenomenon. For example it is a well-known motif that is experienced during hallucinations and near-death experiences. The use of other landscape motifs such as rocks, earth, lightning, clouds and astral constellations is evaluated in both mythological and Christian contexts, for example in the visions of Saint Jerome in the desert and in the practice of shamanism implied in the rock art of the Khoisan of Bushman people. Through this research of the vortex and other landscape motifs various manifestations are revealed: artificial marks in the landscape, which can suggest possible thresholds, and movements of upward and downward directionality, which are suggested over the landscape. The artist‟s discerning choice and use of the medium through which he/she aims to visualise the abovementioned motifs and underlying visual strategies, is also researched. Two factors that influence the medium‟s contribution to the animation of the image come to the fore – light and multi-layering. Light in the medium animates the image in the following ways: the discriminating use of light/lighting in installations can create immersive, deceptive places that stimulate the participant‟s imaginative flight to another reality or can refer to something absent or remote; and in the digital, video and film image light refers to the ignored mechanical aspects at work to create and exhibit images. Multi-layering in installations, digital photomontages and collages awaken visionary associations of imaginary flight through multi-layered spheres in the cultural memory of the landscape, while the discovery of hidden layers of meaning in the image also enables animation. Lastly, the capacity of relevant locations involved in the creation and exhibition of artworks to facilitate the visionary imagination is examined. For example, the studio of the artist can function in the same manner as the remote landscape in which the prophet finds refuge – it encourages a person to cast a visionary gaze over the world. Furthermore it seems as if the sensitive placement and lighting of the artwork in the gallery is capable of evoking a visionary experience in the spirit of the participant as a result of image animation and the productive imagination‟s ability to create a new reality.

Hierdie studie handel oor die onbegryplike verskynsel van die visioenêre ervaring en die moontlike band wat dit deel met die inheemse landskap. Dit word gemotiveer deur my kunstige ondersoek (in die vorm van videokunswerke en digitale fotomontages) van die visioenêre potensiaal wat moontlik opgesluit is in die uitgestrekte Noord-Kaapse landskap. Die probleem aangaande die voorstelling van die visioenêre ervaring word eerstens ondersoek aan die hand van die ontleding van relevante beeldtradisies in die kunsgeskiedenis. Hierdie beeldtradisies sluit in: die mistiese, die sublieme, die apokaliptiese en die mitologiserende tradisies. Die verskillende visuele strategieë wat werksaam is in hierdie beeldtradisies bied insigte aangaande die verskillende wyses waarop die beeld van die landskap se potensiaal as middel tot visioenêre insigte gesuggereer kan word. Sekere van hierdie insigte sluit in: die gebruik van die sirkel en versadigde kleure om mistiese mag in die beeld te suggereer wat soms ‟n visioenêre verklaring fasiliteer; die gebruik van paradoksaliteit, ontkenning (soos somber lig en duisterheid) en sinestetiese kombinasies in die beeld om die kompleksiteit en onbegryplikheid van die visioenêre verskynsel te probeer oorbrug; en die gebruik van figure in die landskap om die teenwoordigheid of verwagting van ‟n aktiewe, chaotiese losbarsting van visioenêre mag in die landskap te suggereer. Die beeld van die uitgestrekte landskap, spesifiek die woestyn, wat suggesties van ewigheid ontlok, se vermoë om ‟n visioenêre losbarsting in die verbeelding wakker te maak, kom na vore – onder meer deur die implementering van die bogenoemde visuele strategieë. Dit wil in so ‟n geval voorkom asof die beeld van die landskap vorentoe spring, so asof dit geanimeerd is. Aby Warburg se opvatting van beeldanimering word ontleed om die beeld se vermoë om die kultuurgeheue in die landskap wakker te maak in die verbeelding, te ondersoek. Die wyse waarop die gebruik van sekere visuele motiewe in beelde van die landskap die animering daarvan kan bevorder, word ontleed. Hierdie visuele motiewe sluit in: die draaikolkvorm as visuele- en landskapmotief soos in warrelwinde en warrelpoele. Die draaikolkvorm se eienskappe van konstante beweeglikheid, transformasie en onstabiliteit se bydrae tot die animering van die landskapbeeld word ondersoek in samehang met die assosiasies wat die draaikolkvorm geniet in die kultuurgeheue van visioenêre verskynsels. Dit is byvoorbeeld ‟n bekende motief wat beleef word tydens hallusinasies en nabye doodservarings. Die gebruik van ander landskapmotiewe soos rotse, grond, weerlig, wolke en sterrekonstellasies word ook ondersoek in mitologiserende asook die Christelike kontekste soos byvoorbeeld by die visoene van die Heilige Jeroen in die woestyn en by die beoefening van sjamanisme soos dit soms gekoppel word aan die rotskuns van die Khoisan of Boesmanstamme. By hierdie ondersoek van die draaikolk en ander landskapmotiewe kom sekere beliggamings aan die lig: mensgemaakte merke in die landskap wat moontlike drumpels suggereer en bewegings van opwaartse en afwaartse gerigtheid wat oor die landskap gesuggereer kan word. Die kunstenaar se deurdagte keuse en gebruik van die medium waarmee hierdie bogenoemde motiewe en onderliggende visuele strategieë gevisualiseer word, word ook ondersoek. Twee faktore wat die medium se bydrae tot die animering van die beeld uitlig, is lig en meervlakkigheid. Lig in die medium animeer die beeld op die volgende wyses: die doelgerigte gebruik van lig/beligting in installasies kan immersiewe, misleidende plekke skep wat die deelnemer verbeeldingryk vervoer na ‟n ander realiteit of verwys na iets wat verwyderd en afwesig is; en in die digitale-, video- en rolprentbeeld verwys lig na die geïgnoreerde meganiese aspekte betrokke by die skepping en ontvangs van beelde. Meervlakkigheid in installasies, digitale fotomontages en collages maak visioenêre assosiasies van ‟n verbeeldingsvlug deur meervlakkige sfere wakker in die kultuurgeheue van die landskap; terwyl die ontdekking van verskuilde lae van betekenis in ‟n beeld ook in staat is om animering te bewerkstellig. Laastens, word die verbandhoudende plekke betrokke by die skepping en ontvangs van die kunswerk se vermoë om die visioenêre verbeelding te fasiliteer, ondersoek. Byvoorbeeld, die ateljee van die kunstenaar kan optree op ‟n soortgelyke wyse as die verlate landskap waarin die profeet toevlug vind – dit moedig ‟n mens aan om ‟n visioenêre blik oor die wêreld te kaats. Verder wil dit voorkom asof die sensitiewe plasing en beligting van die kunswerk in die galery ‟n visioen in die gees van die deelnemer kan verlewendig met die hulp van die uitwerking van beeldanimering en die produktiewe verbeelding se vermoë om ‟n nuwe realiteit te skep.
Dissertation (M.A. (Fine Arts))--University of the Free State, 2015
Keywords: Visionary experience; Landscape; Animation; Imagination; Mystical; Sublime; Apocalyptical; Mythological; Vortex; Rock art; Rocks; Clouds; Medium; Light; Multi-layering; Video; Installation; Studio; Gallery